1994
DOI: 10.1177/004051759406400305
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Moisture Transfer Through Nonwoven Fabrics

Abstract: A theoretical model is demonstrated that provides a reliable prediction of thermal transmission through nonwoven structures. The validity of the model is confirmed in experiments that measure the thermal conductivity of various nonwoven barrier fabrics. The model is used to characterize the relative contribution of heat transfer mechanisms to the total heat transmission. It also provides a good explanation of the roles played by fiber and fabric variables in determining the thermal insulation of nonwoven barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 27 publications
1
48
0
1
Order By: Relevance
“…A lower water vapour resistance is the better the possible evaporation of moisture (sweat) from the wearer's or sleeper's body. The textile having the water vapour resistance up to 5 m 2 Pa W -1 is, according to the literature, a material with very good physiological properties [10,11]. It can be concluded that the static dissipative woven fabric before and after finishing have very good physiological properties and thus great wearing and feeling comfort.…”
Section: Resultsmentioning
confidence: 96%
“…A lower water vapour resistance is the better the possible evaporation of moisture (sweat) from the wearer's or sleeper's body. The textile having the water vapour resistance up to 5 m 2 Pa W -1 is, according to the literature, a material with very good physiological properties [10,11]. It can be concluded that the static dissipative woven fabric before and after finishing have very good physiological properties and thus great wearing and feeling comfort.…”
Section: Resultsmentioning
confidence: 96%
“…Using an analogy with our thermal conductivity model (Equation 1, Part I of this series [ 3 ] ), assuming a vapor pressure gradient across the fabric thickness, and allowing for vapor diffusion through fibers and air interstices, we write a, water vapor diffusion model as follows:…”
Section: Water Vapor Diffusivity Modelmentioning
confidence: 99%
“…where In this model, D, is the diffusion coefficient of water vapor in air and Djll and Dil represent the diffusion I coefficient along the fiber axis and perpendicular to it, Xj is the fiber volume fraction, a is the anisotropy factor (ratio of the number of filaments in the machine and cross machine directions), 4 is the polar orientation angle ( Figure 10 [ 3 ] ), L is the fabric thickness, and d is the fiber diameter. A detailed derivation of this model and the underlying assumptions are given in Appendix A of Part I [3].…”
Section: Water Vapor Diffusivity Modelmentioning
confidence: 99%
“…However, in some applications involving high temperatures, steel fibers, alumina fibers, and/or other similar temperature-resistance materials have also been used for insulation [1,2]. Heat transfer in a fibrous insulation material occurs through conduction, convection, and radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Convection heat transfer can often be neglected since the friction between the fibers and the interstitial fluid may suppress convective motions inside the media. While radiative heat transfer is generally important in high-temperature applications (see [3,4] for instance), conductive heat transfer is often the mechanism by which heat transfers through fibrous materials in temperatures near or below room temperature [2].…”
Section: Introductionmentioning
confidence: 99%